Challenging macho values : practical ways of working with adolescent boys - Salisbury, Jonathan (Falmer Press, 1996)
"Using a mix of the latest theory on boys, men and masculinities and candid accounts of classroom-based practice in an inner-city school, Challenging Macho Values examines the hidden problem of what is happening to our adolescent boys today - why they are disruptive, damaging to themselves and others, and underachieving." "In this book, Salisbury and Jackson challenge the culture of aggressive manliness within which most boys have grown up. They believe that boys aren't driven to violence because of boredom or because 'boys will be boys'. Rather, boys as well as men are being affected by a loss of purpose and direction as the familiar face of men's working and home roles are crumbling. Boys are entering a shifting world of much greater uncertainty and in this collapsing world many boys and young men are feeling lost and confused." "This highly readable, insightful and penetrating book brings to light the key social forces that shape the boys of today - media portrayal of heroic manliness, the emphasis on boys' virility rather than their sexuality, bullying, sexual harassment, verbal insults and putdowns, sport and the making of masculine bodies, and militaristic culture - and suggests practical ways of challenging and changing destructive patterns of behaviour."--Jacket